Lidia Gross, “Bresle şi confrerii sau despre pietatea urbană în Transilvania medievală (secolele XIV-XVI)”, Cluj-Napoca, Argonaut, 2014, 266 p., ISBN 978-973-190-502-8 - ŞTEFAN, Alexandru (Studia Universitatis Babeș-Bolyai Historia, 2015)
Following the two editions of the book Confreriile medievale în Transilvania (secolele XIV-XVI) [“Medieval confraternities in Transylvania (14th – 16th c.)”] and also of several studies regarding the larger theme of the devotional phenomenon for the same time and space context, Lidia Gross brings to the historiographical debate the results of six different researches, reunited into a dense volume. Put under the sign of urban life, a research domain still exotic for the Romanian historical writing, the present work offers several insights on how piety functioned within medieval society. Overall, she aims to outline the general framework of Transylvanian townspeople – men or women, privileged or not – in which their religious life found its most appropriate and strong expression in connexion with the group they were part of, but also with the demands of the era. On the other hand, the six studies can be categorized either according to the sources put under investigation or pursuing the concepts articulated on the basis of their highly critical survey.